ANALYSIS OF IMPLEMENTATION STRATEGIES FOR THE ADOPTION OF E-LEARNING IN PUBLIC SECONDARY SCHOOLS: A CASE OF TRANS-NZOIA WEST SUB-COUNTY, KENYA - Wakasiaka, Mwichabe E.; Mungai, Prof. Chegge Peter; Lwangale, David Wafula; Wekesa, Jane (IJRDO - Journal of Applied Management Science, 2015)
This study focused on the topic Adoption of e-learning in public secondary schools; an analysis of implementation strategies in Trans-Nzoia West Sub-County, Kenya. The study operated with the following objectives: to establish e-learning implementation strategies and to establish the extent of its implementation. Though the Kenya Institute of Education (KIE) developed e-learning Compact Discs (CDs) for eleven (11) subjects in Form 1 and disseminated them to schools in the year 2005, many schools in the Sub-County do not use them to supplement face to face teaching and the chalkboard prompting this study to analyze strategies and extent and of their implementation. The study was guided by the theory of Perceived Attributes (Rogers, 1995) which postulates the way potential adopters judge an innovation. The study was carried out in Trans-Nzoia West Sub-County of Trans-Nzoia County in Kenya. Descriptive Survey research design was used to produce statistical information about aspects of education that interest policy makers and educators (Borg and Gall, 1989). The study targeted 58 secondary schools, 58 principals, 58 Board of Management (BoM) chairpersons, and Heads of Department (HoDs) of the 58 schools. The sample size comprised of Seventeen (17) schools, Seventeen (17) BoM. members, Seventeen (17) principals and One hundred and four (104) HoDs making a total of 155. Instruments of data collection were questionnaire and interview schedules. Descriptive statistics using percentages and frequencies was used to analyze the collected data. The findings reflect the actual state of the adoption of e-learning in secondary schools. The findings revealed that most of the e-learning implementation strategies were lacking in secondary schools in TransNzoia West Sub-County. There was lack of trained teachers, basic structures and no functional computer labs in the area of ICT. The extent of implementation of e-learning in secondary schools in Trans-Nzoia West Sub-County would not be easily established. This was because no school had indeed started adoption of e-learning.